Impact of medium chain fatty acid products and the replacement of commonly used antibiotics in swine feed - Howard, Meagan G.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
This study evaluated the effect of ZnO, carbadox, and medium chain fatty acids (MCFA) on weanling pig growth performance. A total of 360 pigs (DNA 400x200; 5.4 ±0.07kg bw) were used for a 35d growth experiment that were randomly assigned in a grouped completely randomized design. A total of 60 pens with approximately 6 pigs per pen were used. There were 10 pens as the experimental unit per treatment. Phase 1(d0 to 7) and Phase 2 (d7 to 21) included treatment diets and a common diet was fed during phase 3 (d21 to 42). Pigs were weighed weekly as well as feed disappearance and fecal scores collected. Individual treatment diets included: 1) control, 2) 3,000 ppm ZnO in phase 1 and 1,500 ppm ZnO in phase 2, 3) 50 g/ton carbadox, 4) 1% blend of C6:C8:C10, 5) 1% Feed Energy R2 (Feed Energy Corp, Des Moines IA), and 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). The overall treatment (d0 to 19) showed significantly greater (P<0.05) Average Daily Gain (ADG) for ZnO and carbadox than control and R2 diets. Zno, Carbadox and FORMI showed similar (P>0.05) Average Daily Feed Intake (ADFI) in overall treatment and likely accounted for increased ADG. Carbadox, C6:C8:C10, and FORMI showed similar ADG in overall treatment (P>0.05). Overall treatment (d0 to 35) showed ZnO diet ADG significantly higher than R2 (P<0.05). All other diets were similar (P>0.05). Finally, pigs on ZnO and Carbadox showed growth improvement to those without treatment. MCFA diets show comparable growth to leading diets, but more research is necessary to conclude its ability to be a leading additive for the swine industry.
Keywords: Spring 2019